Os fundos de investimento no Brasil de 2008 a 2013: Institucionalidade e interfaces com a política econômica - Adriana Nunes Ferreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper aims to present the main features of an important segment of the Brazilian financial market, the investment funds. These funds, along with insurers and pension funds, constitute the institutional investors or so-called money managers (Minsky, 1989). The arguments are organized as follows: section II focus on the institutional framework (regulation and form of organization) of the segment in Brazil; section III presents an overview of its performance over the analyzed period; the fourth section summarizes the main conclusions of the analysis.
Keywords: G23; G28; 330; institucional investors; investment funds; financial regulation; public debt